Laser Hemorrhoidoplasty Using Reusable Bare Fiber Combined Mucopexy on Grade IV Internal Hemorrhoid: A Case Report - Fadli Robby Amsriza; Rizka Fakhriani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Hemorrhoids are the most common anorectal disease, affecting millions worldwide. Hemorrhoids are categorized as "internal" or "external" based on their proximity to the pectinate line, which separates the upper 2/3 and lower 1/3 of the anus. The hemorrhoidal disease can be treated in various ways, from non-invasive methods like rubber band ligation, cryotherapy, sclerotherapy, laser photocoagulation, and phototherapy to invasive methods like surgical excision for patients with severe symptoms, grade III or IV hemorrhoids, or persistent bleeding. This study described the results of Laser Hemorrhoidoplasty (LHP) using reusable bare fiber combined mucopexy, a diode laser with wavelengths of 980 nm and 1470 nm, specifically gallium aluminum arsenide (GaAIAs). Methods: a case of a 28-year-old male with complaints of rectal prolapse mass one day ago and could not be reinserted with a finger, bleeding while passing stool, and rectal pain with a Visual analog scale was 7. The patient had experienced similar symptoms and had a sclerobanding procedure four years ago. However, it has reappeared in the past year. The patient was diagnosed with grade 4 internal hemorrhoids and underwent Conclusion: Laser hemorrhoidoplasty using reusable bare fiber with combined mucopexy. After the laser hemorrhoidoplasty procedure on day 4, the patient felt no pain, rectal bleeding, rectal lumps, or soiling.